Pastos y forrajes como fuente de alimento para animales en épocas de sequía. - Rubio Fernández, Christel Natalia (2024)
Drought represents a significant challenge for livestock farming, since it reduces the availability of water and forage for animals. Planning and proper management of pastures and forages are essential to ensure animal nutrition in times of drought. This bibliographic review focuses on the exploration of forage conservation techniques, such as haymaking, silage and haylage, with the aim of providing considerable information for animal feeding during the dry season. The research is based on the need to find techniques so that foods are the best for animal consumption and thus do not obtain poor nutrition. Silage differs significantly from haymaking, this being an option for livestock farmers, since it contains a high nutritional value, likewise, offering the advantage of prolonged storage, therefore it is beneficial in situations of drought or others. In relation to production costs, it is worth mentioning that both silage and haylage are affordable alternatives for livestock farmers that can manifest economic and environmental benefits, with haylage being one of the most suitable for livestock farms.